Correction: Do weaner pigs need in-feed antibiotics to ensure good health and welfare? - Alessia Diana; Edgar G Manzanilla; Julia A Calderón Díaz; Finola C Leonard; Laura A Boyle (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0185622.].